2018
DOI: 10.1029/2018jb016004
|View full text |Cite
|
Sign up to set email alerts
|

Interseismic Ground Deformation and Fault Slip Rates in the Greater San Francisco Bay Area From Two Decades of Space Geodetic Data

Abstract: The detailed spatial variations of strain accumulation and creep on major faults in the northern San Francisco Bay Area (North Bay), which are important for seismic potential and evaluation of natural hazards, remain poorly understood. Here we combine interferometric synthetic aperture radar data from the ERS‐1/2 and Envisat satellites between 1992 and 2010 with continuous and campaign GPS data to obtain a high spatial and temporal coverage of ground deformation of the North Bay. The SAR data from both ascendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…We relocate the events in each family separately (e.g., Figure 3), so that only the highest CCC combinations are used. This is a significantly higher number of RE families than identified in the North Bay by "conventional" means- Xu et al (2018), using only long-lived stations, find only 4 RE sequences on the Rodgers Creek fault, compared with 36 in this study (15 confirmed, 7 possible, and 14 pairs; Figure S8)-showing the importance of using the multistation clustering approach. Overall, we find that 59 of our candidate RE families pass this relocation test (hereafter, "confirmed REs"), and that a further 48 families, despite high CCC values, have insufficient data coverage to allow stable relocations ("possible REs").…”
Section: Detecting Repeating Earthquakes Using Multistation Clusteringmentioning
confidence: 52%
See 1 more Smart Citation
“…We relocate the events in each family separately (e.g., Figure 3), so that only the highest CCC combinations are used. This is a significantly higher number of RE families than identified in the North Bay by "conventional" means- Xu et al (2018), using only long-lived stations, find only 4 RE sequences on the Rodgers Creek fault, compared with 36 in this study (15 confirmed, 7 possible, and 14 pairs; Figure S8)-showing the importance of using the multistation clustering approach. Overall, we find that 59 of our candidate RE families pass this relocation test (hereafter, "confirmed REs"), and that a further 48 families, despite high CCC values, have insufficient data coverage to allow stable relocations ("possible REs").…”
Section: Detecting Repeating Earthquakes Using Multistation Clusteringmentioning
confidence: 52%
“…Overall, we find that 59 of our candidate RE families pass this relocation test (hereafter, "confirmed REs"), and that a further 48 families, despite high CCC values, have insufficient data coverage to allow stable relocations ("possible REs"). This is a significantly higher number of RE families than identified in the North Bay by "conventional" means- Xu et al (2018), using only long-lived stations, find only 4 RE sequences on the Rodgers Creek fault, compared with 36 in this study (15 confirmed, 7 possible, and 14 pairs; Figure S8)-showing the importance of using the multistation clustering approach.…”
Section: Detecting Repeating Earthquakes Using Multistation Clusteringmentioning
confidence: 52%
“…We emphasize that the simplified model of seismicity adopted in this study comes at the cost of several limitations, which are summarized below. As friction is not formulated as a rate‐ and state‐dependent variable vanDinther, Gerya, Dalguer, Corbi, et al, ; vanDinther, Gerya, Dalguer, Mai, et al, ), the model does not account for spontaneous nucleation of analog earthquakes and enhanced postseismic creep at high strain rates (Druiventak et al, ; Xu et al, ). This latter process might be influential at the bottom of natural seismogenic zones where viscous dissipation would provide long‐term heating stabilizing the thermal anomaly (Küster & Stöckhert, ; Trepmann & Stöckhert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interferometric synthetic aperture radar (InSAR) data have been successfully used to study earthquake cycle deformation, especially when ground‐based data are not available (Elliott et al, ; Fialko et al, ; Fielding et al, ; Li et al, ; Peltzer, ; Raucoules et al, ; Xu et al, ; Xu et al, ; Zhou et al, ). InSAR data can be inverted to derive finite fault slip models, which are important for understanding of fault geometry, fault slip, and fault frictional properties, as well as for assessing potential regional seismic hazards (Elliott et al, ; Marone, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%